Phenomenological Exploration Of Mother's Experiences Of Birth With Lotus Birth - Tridyawati, Feva; Galaupa, Resi; Ayu Sekarwaty, Niken (International Journal of Science, Technology & Management, 2022)
Lotus birth is a normal delivery process, there is no need to clamp the umbilical cord as usual, let alone cut the umbilical cord, allowing the umbilical cord to separate naturally in newborns. Lotus birth can prevent anemia in newborns, so that the baby still gets a blood supply. through the placenta which contains red blood cells, iron, hormone oxygen and other enzymes. This study aims to understand more deeply the experience of mothers who gave birth with Lotus Birth. The researcher involved 29 participants who were selected through a purposive sampling technique based on (1) mothers who had previous experience of giving birth with the lotus birth method. (2) mothers who gave birth by lotus birth. (3) mothers who agreed were taken as the research sample. (4) mothers who gave birth normally and spontaneously without complications. The interviews were conducted in a formally structured manner and analyzed by descriptive analysis method.